Karolingische Klöster. Wissenstransfer und kulturelle Innovation - Becker, Julia (Materiale Textkulturen, 2015)
Carolingian monasteries were the most important agents for the transfer of knowledge and scientific methods during the early middle ages. This publication examines contemporary vehicles and recipients that were involved in the Carolingian knowledge system and guided the transmission and selection of knowledge. The study focuses on the Abbey of Lorsch with its extraordinary manuscript collection and unique library.